Newtown mitosis a case for the temporal dimension of history as a place making tool - Gouws, Cliff (My University, 2017)
The dissertation Newtown Mitosis investigates the link between the theoretical constructs of time and place, and analyses the potential of urban heritage as a place making tool. The research topic focuses on collective memory as a catalyst for urban regeneration, which ultimately contributes to the production of meaning in our historic urban environments. Though the analysis of various theoretical stances concerning place, placelessness, memory and place-making, a new urban conservation strategy is conceptualised. This strategy focuses on the use-value of urban heritage areas, where the success of commemoration is based on the daily access of memory, rather than museumification or monumentalisation of history. The proposed study area, Newtown, provides the perfect canvas for intervention, in that its historical layers and inherent sense of place is being under-utilised as a conservation strategy. As one of the oldest precincts in Johannesburg, Newtown exemplify rich residential and industrial heritage that conceptually represents an image of technological urban progress. Today this city node stands in isolation, unable to reconnect future visions of growth with its layered history. Furthermore, the temporal dimension of Newtown’s history that currently fuels its inherent urban character is ironically encapsulated in static monuments and time-based relics like the historic Park Halt Station and Museum Africa. Further physical constraints like urban buffers, precinct access, urban security and transportation issues are also focused on. The main research question focuses on how heritage can be used as a place-making tool in Newtown, and thus challenges current urban conservation planning being applied by local government. The dissertation also addresses the commemoration of contested histories, which is a reoccurring theme in various South African cities. The research proposal thus aims at providing urban platforms for mediation, where the temporal layers of history can be utilised to anticipate and inform the future
Submitted in partial fulfillment of the requirements for the degree of Master of Urban Design, (MUD), to the Faculty of Engineering and the Built Environment, University of Witwatersrand